2011
DOI: 10.1007/s00213-011-2188-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics

Abstract: Our present findings suggest that there are sex differences in the prevalence of QTc prolongation and QTc lengthening in schizophrenia. Antipsychotic types are risk factors for QTc prolongation, and risks are substantially higher for clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 32 publications
4
52
4
Order By: Relevance
“…However, this decline in the whole sample was driven by the decreasing per cent of QTc prolongation in China (from 9.5% in 2004 to 0.3% in 2008/2009) and Hong Kong (from 2.4% in 2004 to 0% in 2008/2009). Our finding that 2.4% of patients had QTc prolongation is at the very low end of the range reported from other surveys, in which QTc prolongation in patients with schizophrenia ranged from 0.5% to 38% (Ramos‐Rios et al ., ; Yang et al ., ). The reason for differences between our finding and those from other studies is likely due to a number reasons, including inconsistent cutoff values for QTc prolongation ranging from 420 to 470 ms (Warner et al ., ; Reilly et al ., ), differences in patient characteristics (young versus older adults and Caucasian versus Asian patients), study settings (inpatients versus outpatients), and treatment characteristics (first‐generation antipsychotic (FGA) versus second‐generation antipsychotic (SGA) use, high versus medium/low dose, and comedications use).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, this decline in the whole sample was driven by the decreasing per cent of QTc prolongation in China (from 9.5% in 2004 to 0.3% in 2008/2009) and Hong Kong (from 2.4% in 2004 to 0% in 2008/2009). Our finding that 2.4% of patients had QTc prolongation is at the very low end of the range reported from other surveys, in which QTc prolongation in patients with schizophrenia ranged from 0.5% to 38% (Ramos‐Rios et al ., ; Yang et al ., ). The reason for differences between our finding and those from other studies is likely due to a number reasons, including inconsistent cutoff values for QTc prolongation ranging from 420 to 470 ms (Warner et al ., ; Reilly et al ., ), differences in patient characteristics (young versus older adults and Caucasian versus Asian patients), study settings (inpatients versus outpatients), and treatment characteristics (first‐generation antipsychotic (FGA) versus second‐generation antipsychotic (SGA) use, high versus medium/low dose, and comedications use).…”
Section: Discussioncontrasting
confidence: 76%
“…In a study conducted in China, Yang et al . () reported that the percentage of QTc prolongation in Chinese hospitalized schizophrenia patients was 4.5%, which was somewhat higher than our figure in the whole sample (2.4%) but in the range of Chinese patients between our two surveys (9.5% in 2004 and 0.3% in 2009). Interestingly, the percentage of QTc prolongation has decreased in China during the study period, which may be explained by the widespread use of SGAs and decreased use of FGAs; as compared with FGAs, SGAs have a lower risk of QTc prolongation (Jolly et al ., ; Ray et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to such a predisposition, cardiac electrical activity can be altered by antipsychotic use, resulting in QTc prolongation, even in younger patients, in particular in women 98,99. In adults, QTc prolongation is generally clinically relevant when QTc is >500 milliseconds or when QTc increases by ≥60 milliseconds from drug-free baseline,39 resulting in an increased risk of torsades de pointes and sudden cardiac death (SCD).…”
Section: Methodsmentioning
confidence: 99%
“…aripiprazol, clothiapine, haloperidol; data not depicted). In particular, the administration of clozapine, known to be associated with higher QT-prolongation risk than risperidone [9], had no effect on QT-length (Figure  1B). …”
Section: Case Reportmentioning
confidence: 99%